2005
DOI: 10.1186/1471-2202-6-29
|View full text |Cite
|
Sign up to set email alerts
|

Response of SI cortex to ipsilateral, contralateral and bilateral flutter stimulation in the cat

Abstract: Background: While SII cortex is considered to be the first cortical stage of the pathway that integrates tactile information arising from both sides of the body, SI cortex is generally not considered as a region in which neuronal response is modulated by simultaneous stimulation of bilateral (and mirror-image) skin sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…An early animal study found that SII receives substantial inputs from topographically appropriate regions within the ipsilateral ventrobasal nucleus and from the ipsilateral posterior group (Carvell and Simons, 1987), which indicated that SII in mice may complement the function of SI by helping to define the overall sensory context in which detailed tactile discriminations are made. Our findings suggested that the right SII was involved in both low and high velocities and might play an important role in discriminating the velocity of orofacial tactile stimuli (Carvell and Simons, 1987;Tommerdahl et al, 2005a). Moreover, there was no statistically significant difference in connection strength for the 25 cm/s vs "All ON" conditions.…”
Section: Effects Of Velocitymentioning
confidence: 58%
“…An early animal study found that SII receives substantial inputs from topographically appropriate regions within the ipsilateral ventrobasal nucleus and from the ipsilateral posterior group (Carvell and Simons, 1987), which indicated that SII in mice may complement the function of SI by helping to define the overall sensory context in which detailed tactile discriminations are made. Our findings suggested that the right SII was involved in both low and high velocities and might play an important role in discriminating the velocity of orofacial tactile stimuli (Carvell and Simons, 1987;Tommerdahl et al, 2005a). Moreover, there was no statistically significant difference in connection strength for the 25 cm/s vs "All ON" conditions.…”
Section: Effects Of Velocitymentioning
confidence: 58%
“…In humans, neuroimaging studies using fMRI and MEG have provided evidence of bilateral interactions in SI (Hlushchuk & Hari, 2006;Kakigi, 1986;Kakigi & Jones, 1985;Sutherland & Tang, 2006;Tan et al, 2004;Tommerdahl, Simons, Chiu, Favorov, & Whitsel, 2006). In a recent study, we examined the contribution of SI and SII to the spatial coding of touch at the fingers of the same or different hands, taking advantage of the fMRI adaptation paradigm (Tamè et al, 2012).…”
Section: Direct Evidence For Bilateral Interactions In Si: Brain Imagmentioning
confidence: 99%
“…A second possibility (SI-SI transcallosal projections) is that SI receives ipsilateral somatosensory inputs from contralateral SI, via transcallosal fibres (Allison, McCarthy, Wood, Williamson, & Spencer, 1989;Caminiti et al, 2013;Fabri et al, 2001;Fabri et al, 2005;Fling, Benson, & Seidler, 2013). Finally, a third possibility (SII-SII or SII-SI transcallosal projections) is that cortico-cortical modulations of SI could also emerge via transcallosal connections between homologous SII regions or from heterotopic SII and SI regions (Schnitzler, Salmelin, Salenius, Jousmäki, & Hari, 1995;Tommerdahl et al, 2006).…”
Section: Anatomical Pathways Serving Bilateral Integration In Simentioning
confidence: 99%
“…Most studies of somatosensation concentrate on a single cerebral hemisphere and examine the neocortical representations of tactile signals arising from the opposite, or contralateral, side of the body. However, across species, ipsilateral tactile stimuli have also been shown to evoke changes in population activity of primary (S1) and secondary (S2) somatosensory cortex (Pidoux and Verley, 1979;Tommerdahl et al, 2005;Hlushchuk and Hari, 2006;Lipton et al, 2006;Ferezou et al, 2007;Eickhoff et al, 2008;Plomp et al, 2017;Song et al, 2018), mainly mediated by corticocortical projections via the corpus callosum (Pidoux and Verley, 1979;Picard et al, 1990;Fabri et al, 1999). Yet, surprisingly little is known about the cellular-level specificity of ipsilateral stimulus-evoked activity in S1 and S2, and about its potential role in the neocortical encoding of tactile information during awake somatosensation.…”
Section: Introductionmentioning
confidence: 99%